Simulation and design optimisation of broach tool geometry for enhancing material removal rate. (2018) - Kalyankar, Vivek D.; Pujari, Amey
In this work, broach tool geometry is considered and attempt is made to simulate and optimise the geometry so as to enhance the material removal rate (MRR). Highly efficient DEFORM 3D software is used for simulation and optimisation purpose of broaching tool which is also reported in literatures and being used by reputed industries. The modified tool design is considered for machining of AISI 1045 and brass materials and the optimised tool geometry has reduced the number of broach teeth from 44 to 14 in case of AISI 1045 work material and from 44 to 07 in case of brass material thereby considerably reducing the tool cost. Moreover, the proposed optimum tool geometry has also given considerable improvement in the MRR for both the materials compared to previous results. Hence, the present approach may become useful to the industries to improve the MRR and tool cost.